Total Cross Section of the n+11B Reaction - Galios, G.; Doukelis, G.; Kossionides, S.; Paradellis, T. (HNPS Advances in Nuclear Physics, 2020)
The total neutron cross section of 11Β has been measured from 7.2 to 8.4 MeV. The analysis of all data from the 8Li(α,n0)11Β reaction in combination with the total cross section data can determine an upper limit on the stellar reaction rate of the 8Li(a,n)11Β reaction.